Peri-Implant Diseases - Das, Dipanjan; Shenoy, Nina (Journal of Health and Allied Sciences NU, 2021)
Osseointegrated dental implants have become an increasingly popular modality of treatment for the replacement of absent or lost teeth because of its high rates of long-term survival when used to support various types of dental prostheses. However, complications and implant failure can still occur and are considered by many clinicians as a major obstacle for implant treatment. Biological complications mainly refer to inflammatory conditions of the soft tissues and bone surrounding implants and their restorative components, which are induced by the accumulation of bacterial biofilm. Two clinical varieties may be distinguished: peri-implant mucositis and peri-implantitis. Peri-implant mucositis is a reversible, plaque-induced inflammatory lesion confined to the peri-implant soft tissue unit, whereas peri-implantitis is an extension of peri-implant mucositis to involve the bone supporting the implant. Diagnosing and managing these biological complications is of utmost importance for the implant surgeon and dental practitioner. This review encompasses the etiology, diagnostic aspects, prevention, and management of biological complications.
Keywords: peri-implant mucositis; peri-implantitis; etiology; diagnosis; prevention; treatment